Analysis of the Role of Customer Relationship Management (CRM) in Maintaining Customer Loyalty - Dony Ari Nugroho (Eduvest - Journal of Universal Studies, 2025)
Customer loyalty has an important role in business continuity, considering that loyal customers tend to make purchases more often, provide recommendations, and have a high lifetime value. In the midst of increasingly fierce business competition with a large selection of similar products and services, companies need to maintain customer loyalty to maintain a competitive advantage. One way to maintain customer loyalty is through the implementation of Customer Relationship Management (CRM). This study aims to analyze the role of CRM in maintaining customer loyalty. This study uses a qualitative approach with data collection techniques through literature studies. After the data is collected, data analysis is conducted through relevant data screening and data presentation, and a conclusion is drawn. The study results show that CRM is an important investment for companies that want to maintain customer loyalty. Companies can understand customer needs, provide personalized experiences, and improve service quality through CRM. CRM helps companies build strong, long-term relationships with customers, which ultimately positively impacts business growth and company sustainability. Therefore, implementing CRM can be used as an effective business strategy for companies amid increasingly fierce market competition.